The Effect of TCNE and TCNQ Acceptor Units on Triphenylamine‐Naphthalenediimide Push‐Pull Chromophore Properties. Issue 18 (10th May 2021) - Srinivasa Rao, Pedada; Brixi, Samantha; Shaikh, Dada B.; Al Kobaisi, Mohammad; Lessard, Benoît H.; Bhosale, Sidhanath V.; Bhosale, Sheshanath V.
Abstract: Asymmetrical and symmetrical push‐pull chromophore‐based on triphenylamine (TPA) donors and naphthalenediimide (NDI) acceptors are designed and successfully synthesized via [2+2] cycloaddition‐retroelectrocyclization (CA‐RE) reaction with well‐known electron‐accepting tetracyanoethylene (TCNE) and 7, 7, 8, 8, ‐tetracyanoquinodimethane (TCNQ) groups. The novel series of compounds NDI‐TPA‐1 to NDI‐TPA‐6 were characterized to identify the influence of the TCNE and TCNQ π‐conjugated linkers on the optical, electrochemical, and electronic properties of these molecules. We found that in dichloromethane the NDI‐TPAs 1, 4, 5, and 6 display absorbance peaks at increasing wavelengths 605, 641, 646, and 645 nm, respectively. We demonstrated that through simple chemical modification we could drop the lowest occupied molecular orbital of NDI‐TPA‐1 to 6 . Furthermore, NDI‐TPA‐1 to 6 were integrated into organic thin‐film transistors (OTFTs) via spin‐coating technique, and charge transfer properties were investigated. We found that the choice of the functional group led to either p‐type, n‐type, or ambipolar characteristics. Abstract : We developed six new naphthalenediimide based chromophores bearing TCBD and DCNQCNM and their influence on optoelectronic and electronic properties. Organic thin‐film transistor characteristics based on this electron‐deficient molecular architecture were demonstrated on bottom gate bottom contact transistors.